Gender balance in national parliament: voters' perceptions towards the gender corrective mechanism in Malta. Issue 4 (19th May 2022) - Bezzina, Frank; Brown, Maria; Marmarà, Vincent-Anthony
ABSTRACT: This quantitative study queried perceptions of the gender corrective mechanism as part of a broader parliamentary gender balance reform programme in Southern European, EU island state Malta. A representative sample ( n = 435) of the Maltese electorate showed support for increased representation of women (88.5%) and the integration of the gender corrective mechanism (66.5%); but manifested a preference for other measures, namely childcare facilities, full-time backbenchers and more females in the electoral commission. Consequently, should the preferred measures not be sufficiently addressed, the reform risks falling short of sustainable development. The study adds to literature about how the electorate engages with more representative parliaments when this is targeted using constitutional amendments. Recommendations include financial support for parties to attract candidates from under-represented genders, and an effective public information campaign that explains the gender corrective mechanism as a safety-valve that compensates for any gaps in representation that the other reform pillars fail to achieve.